Spacer layer design for efficient fully printable mesoscopic perovskite solar cells. Issue 51 (20th September 2019) - Liu, Tongfa; Xiong, Yuli; Mei, Anyi; Hu, Yue; Rong, Yaoguang; Xu, Mi; Wang, Zheng; Lou, Lingyun; Du, Dongjie; Zheng, Shizhao; Long, Xia; Xiao, Shuang; et al.
Abstract : Key principles and reasonable routes are proposed to advance the spacer layer design for fully printable mesoscopic perovskite solar cells. Abstract : The spacer layer is a key component of fully printable mesoscopic perovskite solar cells, but its precise characteristics are far from being understood in relation to the device design. In the present work, we perform a detailed systematic study on the effects of spacer parameters, such as size of building blocks, layer thickness, etc., on properties of the perovskite filler, insulating ability and performance of fully printable mesoscopic perovskite solar cells by combining the techniques of time-resolved photoluminescence, high-resolution TEM, insulating resistance measurements, impedance spectroscopy and J – V characteristics. Drawing on the deep understanding from these studies, we formulate key principles, which are anticipated to guide the design of the advanced spacer layer for fully printable mesoscopic perovskite solar cells.